2023
DOI: 10.3389/fpubh.2023.1084005
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of osteoporosis in China, a community based cohort study of osteoporosis

Abstract: BackgroundOsteoporosis has already been a growing health concern worldwide. The influence of living area, lifestyle, socioeconomic, and medical conditions on the occurrence of osteoporosis in the middle-aged and elderly people in China has not been fully addressed.MethodsThe study was a multicenter cross-sectional study on the middle-aged and elderly permanent residents, which gathered information of 22,081 residents from June 2015 to August 2021 in seven representative regions of China. The bone mineral densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…This may be due to the higher BMI of patients with degenerative lumbar spine disease included in this study [ 28 ]. Clinical studies have found that diabetic patients are more prone to fracture although their BMD is higher than non-diabetic patients [ 29 ]. There was no statistically significant difference in the prevalence of underlying diseases (hypertension/diabetes) among the three groups of patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the higher BMI of patients with degenerative lumbar spine disease included in this study [ 28 ]. Clinical studies have found that diabetic patients are more prone to fracture although their BMD is higher than non-diabetic patients [ 29 ]. There was no statistically significant difference in the prevalence of underlying diseases (hypertension/diabetes) among the three groups of patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of regional variances revealed that, to a certain extent, the interest search trend of the Baidu Index may indicate the actual nationwide healthcare trend of osteoporosis. The amount of osteoporosis retrieved in northern China was much higher than that in southern China, which may reflect the geographical distribution pattern of osteoporosis incidence and prevalence in China, reflecting the influence of environmental differences on bone formation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the fracture risk continues to increase, especially in Asia 1 , 2 . Among elderly and middle-aged Chinese residents, 33.49% develop osteoporosis 3 . The disease commonly manifests in individuals aged 50 years and often goes unnoticed until a fracture occurs.…”
Section: Introductionmentioning
confidence: 99%